Computer science club for girls and boys – a survey study on gender differences. Issue 4 (2nd October 2021) - Vrieler, Tina; Nylén, Aletta; Cajander, Åsa
ABSTRACT: Background and context : This study investigates differences in views of girl and boy members of a CS club.Objective :Understanding differences in the views of girls and boys regarding perceived parental attitudes and values, social support, appreciation of CS, and engagement in science and CS. Understanding differences in girls' and boys' view of CS, and future study and work aspirations related to science/CS.MMethod : A survey was distributed to all members of a CS club. 115 boys and 39 girls aged 9–16 completed the survey, yielding a response rate of 16.8%.Findings : Similar parental support was perceived by both genders, although girls are less likely to appreciate CS and to aspire to work or study CS. Girls tend to primarily talk to family about CS and science. Girls and boys have a similar perception of CS, but their motivation for wanting to work with CS varied.Implications :Having support, a broad understanding of CS, and a personal interest are critical aspects when it comes to girls' participation in CS, but these are insufficient in making girls aspire to work or study CS. Educators need to reflect on other aspects of CS education that can promote girls' aspiration in CS.